Identification and characterisation of fluorescent substances in spent dialysis fluid. Issue 9 (September 2020) - Meibaum, Jörn; Krause, Silvie; Hillmer, Hartmut; Marcelli, Daniele; Strohhöfer, Christof
Patients who suffer from end-stage renal disease require renal replacement therapy, including haemodialysis. While applying extracorporeal blood treatment, uraemic toxins accumulated in the patients' blood pass into a physiological solution, the dialysis fluid. Thus, important information about the patient's health status can be obtained by analysing the spent dialysis fluid. To make use of this information, corresponding analysis concepts must be developed. In this context, this article reports the analysis of fluorescence in spent dialysis fluid. Excitation and emission maxima of fluorescence in spent dialysis fluid were recorded, and the main fluorescent substances were identified and quantified using high-performance liquid chromatography analysis. Fluorescence in spent dialysis fluid has two prominent excitation maxima at λex1 = 228 nm and λex2 = 278 nm. However, both excitation maxima cause emission with maxima at λem = 350 nm. Identification of fluorescent substances using high-performance liquid chromatography showed that the main contributors to the overall fluorescence in spent dialysis fluid are tyrosine, tryptophan, indoxyl sulphate and indole-3-acetic acid. However, these substances are responsible for only one-third of the overall fluorescence of spent dialysis fluid. A large number of substances, each of which contributes only to a small part to the overall fluorescence, emit the remaining fluorescence.